From Sprawl to Sky: Legal Barriers to Affordable Vertical Housing Amid Landed Home Preferences in Semarang - Tan, Wei Jie; Legiman, Aprilia Puspitasari Putri; Hakim, Aiman Abd; Robbi, Muhammad Azka (Indonesian Journal of Agrarian Law, 2025)
Public preference for landed housing in Semarang City poses a serious challenge to the development of affordable vertical housing, such as apartments. This article analyzes the factors influencing this preference and examines the legal regulations regarding landed housing in Indonesia, particularly in Semarang City. Through a normative legal approach and qualitative data, it is found that cultural factors, social status, land ownership, and minimal public awareness of landed housing influence the low public interest in apartments. Meanwhile, legal regulations regarding landed housing are scattered across various regulations and have not provided concrete solutions to the accessibility of affordable landed housing. Therefore, regulatory harmonization and responsive public policy interventions are needed to address the dynamic housing needs in urban areas like Semarang.